Christian Elite in Al-Karak and their Political Role between 1893 and 1946 AD: A Historical Study - Al Btoush, Bassam Abdelsalam (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aims to introduce the elite Christians in Al-Karak between 1893 and 1946 and to identify the factors and conditions that caused and influenced their formation. It also intends to clarify their political roles in public life through successive political eras in Al-Karak during the aforementioned period. Methods: The study combines the historical method (which traces the historical evolution of the elite Christians’ roles within a spatial and temporal framework) with the descriptive analytical approach (which helps to understand the form factors of the elite Christians and their roles in public life). The study relies on several primary sources such as personal interviews, unpublished private papers by the political elites of Al-Karak, the proceedings of the Jordanian legislative council 1929-1946, British documents, Arab newspapers issued over the study period, and a number of other references in both Arabic and English. Results: It became evident that the elite Christians in Al-Karak consisted of prominent figures, young people who received different educational degrees, and people who were committed to administrative work for successive authorities who ruled the region over the study period. Their formation was affected by administrative, political, and socio-economic transformations; the spread of education; and the gradual opening up to the outside world. The results showed that those elites played important roles in public life in all political eras and integrated authentically with the overall public life in their society. Conclusions: Over the study period, the elite Christians in Al-Karak provided a model for the formation and development of the Jordanian elites and played influential roles that became more evident concomitantly with the development of political, social, and economic conditions in the nation-state era. This study invites to examine the elite Christians’ roles in Al-Karak over the Kingdom’s independence era after 1946 AD.